Magnetic Conjugacy of Pc1 Waves and Isolated Proton Precipitation at Subauroral Latitudes: Importance of Ionosphere as Intensity Modulation Region. Issue 5 (6th March 2021) - Ozaki, Mitsunori; Shiokawa, Kazuo; Horne, Richard B.; Engebretson, Mark J.; Lessard, Marc; Ogawa, Yasunobu; Hosokawa, Keisuke; Nosé, Masahito; Ebihara, Yusuke; Kadokura, Akira; Yagitani, Satoshi; Miyoshi, Yoshizumi; et al.
Abstract: Pc1 geomagnetic pulsations, equivalent to electromagnetic ion cyclotron waves in the magnetosphere, display a specific amplitude modulation, though the region of the modulation remains an open issue. To classify whether the amplitude modulation has a magnetospheric or ionospheric origin, an isolated proton aurora (IPA), which is a proxy of Pc1 wave‐particle interactions, is compared with the associated Pc1 waves for a geomagnetic conjugate pair, Halley Research Base in Antarctica and Nain in Canada. The temporal variation of an IPA shows a higher correlation coefficient (0.88) with Pc1 waves in the same hemisphere than that in the opposite hemisphere. This conjugate observation reveals that the classic cyclotron resonance is insufficient to determine the amplitude modulation. We suggest that direct wave radiation from the ionospheric current by IPA should also contribute to the amplitude modulation. Plain Language Summary: The amplitude of electromagnetic ion cyclotron (EMIC) waves in the magnetosphere, which are observed as Pc1 waves on the ground, is an important parameter for characterizing the loss of energetic particles. The generation region of EMIC waves is well understood as being the magnetic equator, but the amplitude modulation region is not well‐established due to wide horizontal Pc1 wave propagation in ionospheric ducts. Here we compare the properties of Pc1 waves and isolated proton precipitation from an ideal geomagnetic conjugate observation at Halley Research Base in Antarctica and Nain in Canada. By visualizing the cyclotron resonance region in the magnetosphere as an isolated proton aurora (IPA), the ambiguity of the horizontal propagation effects of Pc1 waves in the ionosphere is ideally removed. The observed IPA in the northern hemisphere has remarkable similarities with Pc1 waves in the same northern hemisphere, but not the southern hemisphere, providing evidence that the temporal variations of wave amplitude can be characterized by an ionospheric current induced in the IPA, and cannot be described only by a classical cyclotron resonance mechanism at the magnetic equator. Therefore, this study suggests that an IPA ionospheric current contributes to temporal modulations of Pc1 waves on the ground. Key Points: Similarities and differences of magnetic conjugacy between Pc1 waves and isolated proton precipitation are reported The proton aurora shows a strong similarity with Pc1 waves in the same hemisphere, not characterized by classical cyclotron resonance This study suggests the importance of ionosphere for Pc1 waves by an ionospheric current modulation of an isolated proton aurora